The Mediating Role of Self-Injurious Thoughts in the Relationship Between Psychological Distress and Death Obsession with Suicide Attempts Among Adolescents Experiencing War Anxiety - Ameri, Zeinab; Daram, Maryam; Asobar, Shida; Khazael, Habibeh; Gol Aflak, Ziba; Ahmadipour, Alireza (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: This study aimed to examine the mediating role of self-injurious thoughts in the relationship between psychological distress and death obsession with suicide attempts among adolescents experiencing war anxiety.Methods and Materials: This applied study was conducted using a correlational design based on structural equation modeling. The statistical sample consisted of 215 adolescents aged 15 to 18 years living in Mahshahr, who were selected through voluntary sampling. The research instruments included the Shomali and Barkhordari War Anxiety Questionnaire, the Osman et al. Suicide Attempt Questionnaire, the Abdel-Khalek Death Obsession Scale, the Kessler et al. Psychological Distress Scale, and the Shomali and Barkhordari Self-Injurious Thoughts Questionnaire. Data were analyzed using Pearson correlation and structural equation modeling through SPSS version 27 and AMOS version 24.Findings: The inferential results showed that the direct effects of psychological distress and self-injurious thoughts on suicide attempts were positive and statistically significant. The direct effects of psychological distress and death obsession on self-injurious thoughts were also positive and statistically significant. In addition, the indirect effects of psychological distress and death obsession on suicide attempts through self-injurious thoughts were positive and statistically significant. However, the direct effect of death obsession on suicide attempts was not significant in the final structural model. These findings confirmed the mediating role of self-injurious thoughts in the relationship between psychological distress, death obsession, and suicide attempts among adolescents experiencing war anxiety.Conclusion: The findings indicate that self-injurious thoughts are a key cognitive-emotional mechanism linking psychological distress and death obsession to suicide attempts in adolescents exposed to war-related anxiety. Therefore, preventive and therapeutic interventions should prioritize the early identification and modification of self-injurious thoughts, especially among vulnerable adolescents experiencing psychological distress and death-related preoccupations.